(untitled) (Experimental biology, 2020)
The dominant types of infections that cause microbial inflammation, which leads to the damage of tubulointerstitial tissue and pyelocytic system in the kidneys are considered in the article. The study examined 88 bacterial cultures from the urine of children aged 1 month to 17 years with UTIs using special microbiological studies. Sectoral inoculation to endo medium and blood agar was performed and species composition and quantitative parameters of intestinal microflora were determined by the degree of bacteriuria. Sensitivity of isolated strains of microorganisms to antimicrobial drugs was determined by persistent markers. Methods of processing obtained results were evaluated by variational statistics, difference accuracy of the analysis was determined by Student-Fisher criteria. According to the research, the largest number of dominant bacterias is related to Staphylococcus (30,6%) relatives, especially the types in it: S.aureus (11,1%), S.epidermidis (48,1%) and S.saprophyticus (37,1%), S.intermedius (3,7%). It is defined that the prevalence of bacterial cultures in children depends on their age peculiarities, sex and time of the year. In particular E.Coli strains, which cause renal inflammation are more dominant among the boys and girls in summer, Enterococcus faecalis is dominant in the fall and Candida fungi relative representatives are spread widely among the boys in all season. Staphylococcus epidermidis strain is the most prevalent among girls in spring. As a result of the research, it is defined that the Staphylococcus epidermidis was dominant. The sensitivity of Staphylococcus epidermidis strain to antibiotic susceptibility and resistance was defined and it is revealed that the highest sensitivity to cefotaxime (98,6%), cefazolin (97,8%), cefuroxime (95,5%), amikacin (100%), oxacillin (85,3%), imepinem (87,5%) was very high. The antibiotic resistance of some types of pathogens of the urinary system in children, namely the studied opportunistic bacteria, also depend on the physiology of an individual organism.Key words: renal infection, pyelonephritis, microbial biocenosis, bacteriuria, tubulointerstitial inflammation, immunity